Valor percibido y lealtad del consumidor de productos saludables en el mercado peruano, Lima 2021 - Cisneros Sandoval, Wendy Elizabeth (2021)
The study aims to know the relationship between perceived value and consumer loyalty to healthy products. A cross-sectional correlational study was carried out through the questionnaire applied to 417 consumers, the results show that there is a significant relationship between the study variables; Likewise, it was identified that the consumers of the company under study present the highest percentage of perceived value at a medium level, followed by the low level and finally the lowest percentage shows a high level of perceived value; Likewise, according to the type of customers, the highest percentage are promoters and the lowest corresponds to detractor consumers. In this sense, it is recommended to strengthen the functions of marketing.